A 76db 828nv/âˆšHz Low Noise Bio Signal OTA For Neural Signal Recording Applications - Vijay Mythry, Sarin; Jackuline Moni, D (International Journal of Engineering and Technology, 2018)
The low frequency, low amplitude biomedical signals which created a tremendous demand amongst clinicians and neuroscience researchers are to be amplified in the range of millihertz to kilohertz by rejecting the dc offsets. This research article presents a Bio Signal OTA (Bio-OTA) with 76dB gain, 828nV/ 16Hz"> noise and 390nW power is designed in 90nm CMOS process and also a brief survey on the different types of OTAs used for neuro recording applications is discussed. The Wilson current mirror is used to design 1volt Bio-OTA. The Common mode rejection ratio (CMRR) is obtained as 75dB, power supply rejection ratio (PSRR) is above 88dB and gain bandwidth product (GBW) is 223MHz.Â Â